2015
DOI: 10.1016/j.jff.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Acute supplementation with blackcurrant extracts modulates cognitive functioning and inhibits monoamine oxidase-B in healthy young adults

Abstract: Newcastle University ePrints -eprint.ncl.ac.uk Watson AW, Haskell-Ramsay CF, Kennedy DO, Cooney JM, Trower T, Scheepens A. Acute supplementation with blackcurrant extracts modulates cognitive functioning and inhibits monoamine oxidase-B in healthy young adults. Abstract 42Background: Berry fruit have been shown to convey a number of benefits in animal models; 43including improvements in cognitive performance, slowing of cognitive decline and 44 neuroprotection. These findings, along with epidemiological eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(148 citation statements)
references
References 46 publications
4
127
0
Order By: Relevance
“…A crossover study [19] found that high anthocyanin cherry juice consumption did not result in any significant acute effects on a battery of cognitive tests in either younger or older adults. Contrary to this, Watson et.al, (2015) [20] observed a cognitive benefit of acute blackcurrant supplementation in healthy younger adults possibly explained by an association between monoamine oxidase (MAO) inhibition and improved attention. There is a possibility that the inhibition of MAO have positive effects on monoaminergic neurotransmission during cognitive performance [21].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…A crossover study [19] found that high anthocyanin cherry juice consumption did not result in any significant acute effects on a battery of cognitive tests in either younger or older adults. Contrary to this, Watson et.al, (2015) [20] observed a cognitive benefit of acute blackcurrant supplementation in healthy younger adults possibly explained by an association between monoamine oxidase (MAO) inhibition and improved attention. There is a possibility that the inhibition of MAO have positive effects on monoaminergic neurotransmission during cognitive performance [21].…”
Section: Introductionmentioning
confidence: 94%
“…The precise mechanism by which anthocyanins affect cognition is still not clear but seems to be dependent on the exposure period. Acute effects on cognition are believed to be as a result of increased cerebrovascular blood flow and possibly monoamine oxidase (MAO) inhibition which has been shown to improve cognitive performance [14,20]. Following consumption of high anthocyanin fruit/juice, evidence shows that peaks in cerebral blood flow, vasodilation, and anthocyanin metabolite availability is detectable within 2h post consumption [17].…”
mentioning
confidence: 99%
“…Watson et al . compared three conditions (placebo versus powdered blackcurrant extract with 7.7 mg anthocyanins kg −1 versus blackcurrant juice with 8 mg kg −1 , based on body weight) on acute cognition in 36 young adults by administering tasks seven consecutive times over 65 min after consumption of the beverages. Significant improvements in accuracy were reported, as measured by the rapid visual information processing test ( P = 0.011), when participants consumed the blackcurrant extract versus placebo, as well as improvements in reaction time for some repetitions (1, 4 and 7) on the digital vigilance task compared to baseline tests ( P = 0.044) for blackcurrant juice or extract versus placebo.…”
Section: Resultsmentioning
confidence: 99%
“…Statistical pooling of the data from the seven studies considered eligible for the review (39)(40)(41)(42)(43)(44)(45) was not possible because of the large clinical and methodological diversity of the studies. This heterogeneity resulted from variability in the characteristics of the participants and type of intervention (including food sources and dose of anthocyanins), varying study designs and study duration, as well as differences in choice of cognitive outcomes.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Clinical trials have demonstrated improved attention following flavanol ingestion compared to placebo in a dose-related fashion [94, 95]. A double-blind, controlled, cross-over trial using blackcurrant extracts demonstrated improvement on alerting and orienting but not executive tasks of attention [96]. This finding, however, has not been consistently reproduced with different flavonoid-rich foods [97].…”
Section: Enhancing Attention Using Diet and Lifestylementioning
confidence: 99%